Povezanost telesne pripravljenosti z mišično-skeletnimi težavami pri pisarniških delavcih - Kavčič, Jerca (Šport (Ljubljana), 2022)
Sedentary workplaces pose a significant risk of developing chronic diseases. Sitting that extends into a person’s leisure time further increases the risk. Office workers are often less physically fit, which can lead to various impairments. Our sample was consisted of 30 office workers (17 men and 13 women) from companies Domel d. o. o. and Saloni pohištva Prevc and was analysed using anthropometric measurements, functional ability measurements and an online questionnaire. Employees most often suffer from shoulder problems (50%), lower back problems (50%) and neck problems (43%). In the mobility tests, deficiencies were particularly pronounced in some tests of leg and arm strength, and men also showed lower body mobility. We found several statistically significant associations, most of which were inversely proportional, between functional test scores and the problems in a specific part of the body perceived by the subjects in the last 12 months. Subjects with better shoulder and neck mobility reported less problems in the wrist/arm area (women) and upper back (men). Poorer hip mobility also resulted in more problems in the lower back (women) and ankle (men). The only statistically significant correlation between strength and musculoskeletal problems is found in the male part of the sample, between different tests of limb strength and problems in the knees and ankles. The results suggest that more promotion of regular physical activity is needed, both in the form of daily exercise breaks at work and leisure-time physical activity. Further studies, with larger sample sizes and more variables, are definitely needed to be able to speak more precisely about strategies to prevent the risks of sedentary jobs.
Keywords: mišičnoskeletni sistem; pisarniški delavci; sedeče delo; šport; telesna pripravljenost